2018
DOI: 10.1152/ajprenal.00495.2017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of biliverdin reductase-A promotes lipid accumulation and lipotoxicity in mouse proximal tubule cells

Abstract: Obesity and increased lipid availability have been implicated in the development and progression of chronic kidney disease. One of the major sites of renal lipid accumulation is in the proximal tubule cells of the kidney, suggesting that these cells may be susceptible to lipotoxicity. We previously demonstrated that loss of hepatic biliverdin reductase A (BVRA) causes fat accumulation in livers of mice on a high-fat diet. To determine the role of BVRA in mouse proximal tubule cells, we generated a CRISPR targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…In the present study, the loss of BVRA from WAT resulted in a reduction of mitochondria number. This result is consistent with previous studies in which the deletion of BVRA in both cultured renal proximal tubule cells, as well as cultured hepatocytes, resulted in the decrease in mitochondrial number, mitochondrial membrane potential, oxygen consumption, and extracellular acidification rate [66,67]. Furthermore, the loss of BVRA was shown to decrease the expression of several mitochondrial complex subunit genes as well as mitochondrial dynamin-like GTPase (Opa1), which codes for a protein of the inner mitochondrial membrane regulating mitochondrial stability and energy output [67].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the loss of BVRA from WAT resulted in a reduction of mitochondria number. This result is consistent with previous studies in which the deletion of BVRA in both cultured renal proximal tubule cells, as well as cultured hepatocytes, resulted in the decrease in mitochondrial number, mitochondrial membrane potential, oxygen consumption, and extracellular acidification rate [66,67]. Furthermore, the loss of BVRA was shown to decrease the expression of several mitochondrial complex subunit genes as well as mitochondrial dynamin-like GTPase (Opa1), which codes for a protein of the inner mitochondrial membrane regulating mitochondrial stability and energy output [67].…”
Section: Discussionsupporting
confidence: 93%
“…If BVRA is not found in mitochondria, then why does the loss of BVRA have such a great impact on mitochondrial function? There are several potential mechanisms by which this may occur, including increased reactive oxygen species production in response to BVRA deletion [19,66,68,69]. In the present study, decreases in the metabolite of BVRA, bilirubin, may be responsible for this observed effect on mitochondria number in Blvra FatKO .…”
Section: Discussionmentioning
confidence: 51%
“…Current studies have shown that abnormal lipids in blood lead to the accumulation of ectopic lipids, which can be deposited in almost all cell types from mesangial cells to podocytes and proximal tubular epithelial cells [29]. Lipid-induced mitochondrial damage may also be more lethal to proximal tubule cells [30]. High cholesterol causes macrophage infiltration and foam cell formation in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive RSF and PRF may also cause lipotoxicity owing to the accumulation of intracellular triglycerides and toxic metabolites such as ceramides 57,58 . The mechanisms by which ectopic fat in the kidneys causes injury are still unclear, but increased levels of reactive oxygen species (ROS), mitochondrial dysfunction and endoplasmic reticulum stress may be important contributors.…”
Section: Renal Compressionmentioning
confidence: 99%